Stability in badminton players - A review - Vora, M.; Ranawat, D.; Arora, M. (Advances in Orthopedics and Sports Medicine, 2019)
Stability is the ability to maintain or control joint movement or joint position, in the static as well as dynamic state. Improvement in stability could help maintain body control and proper posture positions during play. Accordingly, the study was proposed to analyze stability in junior badminton players and understand its importance. A total of 106 players from South Asia between the ages of 8 and 15 years were analyzed and static, dynamic, and pelvic stability was recorded. Our study showed that there was significant difference in pelvic stability. There needs to be a greater focus on stability training as part of the development of junior badminton players.